Influence of social context on the pain perception: The effect of the passive observer's distance - Modić Stanke, Koraljka (Array, 2008)
Some previous research has shown that the presence of passive observer in unpleasant (painful) situation increases pain tolerance. However in such research no attention was paid to the spatial distance of the passive observer from the participant experiencing pain. The goal of this research was to test whether and in what way is the effect of the social context on the experience of pain moderated by spatial distance of the passive observer from the participant. Unpleasant (painful) stimuli were caused by the flow of warm air. Variables measured in this research were pain threshold and tolerance, as well as evaluations of intensity and discomfort of stimuli, and some physiological indicators (pulse, blood pressure, temperature). All participants (N = 36) have passed through two experimental situations - with and without the presence of the passive observer ; the only difference being that the spatial distance of the passive observer from one half of the participants (N = 18) was small, while the distance of the passive observer from the rest of the participants (N = 18) was greater. The research results did not confirm statistically significant analgesic effect of the passive observer who was at a greater spatial distance from participants to any pain measure (although such trend was present in pain threshold and tolerance) but did show significant opposite effect of a passive observer at very close distance - his presence lowering pain threshold and tolerance. Such results suggest the potential importance of including personal space as a variable in testing the experience of pain.